Particle acceleration in an MHD-scale system of multiple current sheets - Nakanotani, Masaru; Zank, Gary P.; Zhao, Lingling (Frontiers in Astronomy and Space Sciences, 2022)
We investigate particle acceleration in an MHD-scale system of multiple current sheets by performing 2D and 3D MHD simulations combined with a test particle simulation. The system is unstable to the tearing-mode instability, and magnetic islands are produced by magnetic reconnection. Due to the interaction of magnetic islands, the system relaxes to a turbulent state. The 2D (3D) case both yield -5/3 (-11/3 and -7/3) power-law spectra for magnetic and velocity fluctuations. Particles are efficiently energized by the generated turbulence, and form a power-law tail with an index of -2.2 and -4.2 in the energy distribution function for the 2D and 3D case, respectively. We find more energetic particles outside magnetic islands than inside. We observe super-diffusion in the 2D (t^2.27) and 3D (t^1.2) case in the energy space of energetic particles.